Prediksi Kandungan Pati Pepaya IPB9 Selama Penyimpanan dengan Spektroskopinir - Nur Arifiya (Universitas Indraprasta PGRI Jakarta, 2017)
The parameters of ripe papaya quality consisting of starch content, total soluble solid and water content must be measured by conductinga time-consuming and destructivelychemical analysis. NIR spectroscopy isa non-destructive, accurate, fast methodthat can substitute the such chemical analysis. This study aims to predict starch content, total soluble solid, and water content using NIR spectroscopy. 60 pieces ofpapaya of IPB 9 varietyat the part of top, middle, and bottom was measured with 3 replications. Starch content can be well predicted by NIR spectroscopy with pre-treatment of combination between msc and dg1, as indicated by the model generated by the R, SEC, SEP, CV, and RPD of 0.90, 0.17% 0.16%, 10.95%, and 2.15 respectively. Total soluble solid can bewell predicted by NIR spectroscopy with pre-treatment msc R, SEC, SEP, CV, and RPD, as indicated by 0.90, 0.124%, 0123%, 4.85%, and 2.27 respectively. Similarly, the water content can be well predicted by NIR spectroscopy with pre-treatment dg1 R, SEC, SEP, CV, and RPD, as indicated by 0.84, 0.03%,0.04%, 0.43%, and 1.85 respectively